Intercropping Between Corn and Urochloa brizantha Managed with Mesotrione Underdoses - MARTINS,D.A. (2019)
ABSTRACT: Corn and forage intercropping system has been commonly used for pasture establishment or renewal. In addition, the use of reduced doses of herbicides selective to corn has facilitated coexistence by reducing competitiveness against forage species. This study aimed to evaluate the effects of mesotrione underdoses in a corn and Urochloa brizantha intercropping on weed population dynamics, corn yield, and forage performance and nutritional quality. For this purpose, five mesotrione doses were tested (0.0, 9.6, 19.2, 38.4, and 57.6 g ha-1) in corn and forage intercropping and monocultures. Individual density and weed dry matter were influenced by mesotrione doses, intercropping, and precipitation distribution over the evaluated period in the intercropping and pasture. In intercropping, Alternanthera tenella and Commelina benghalensis were the most important species because they could not be controlled by the herbicide. After intercropping, A. tenella and C. benghalensis presented higher relative importance (RI) in the formed pasture during the rainy season, while Conyza bonariensis and A. tenella presented the highest RI during the dry season. Corn grain yield was not affected by the presence of grass, but forage yield was affected by the competition with corn. Mesotrione doses did not affect the yield and nutritional quality of the forage. The effects on mineral matter, crude protein, and acid detergent fiber in the forage were due to the coexistence with corn when compared to the control grown in monoculture.